PRAKTIK ORANGTUA DALAM PENGAWASAN PERGAULAN REMAJA GUNA MENCEGAH KEHAMILAN TIDAK DIINGINKAN (KTD) - Utami, Fitriana Putri (Care : Jurnal Ilmiah Ilmu Kesehatan, 2019)
Adolescence is a period of transition from childhood to adulthood accompanied by physical and hormonal changes. Sexual maturity in adolescence causes the emergence of sexual interest and high curiosity about sexuality. This makes adolescents very vulnerable to lead to premarital sexual behavior and the occurrence of unwanted pregnancies. This study aims to find out the practices of parents in providing adolescent social risk management at unwanted pregnancy. This research is a qualitative study with a case study approach. The informants in this study were seven people who were selected purposively with the criteria of parents who had teenage boys and girls (12-21 years) and were known to have been dating. Data validation uses triangulation of sources, namely teenagers who have been dating as many as three people. Data is taken by independent interview and analyzed using content analysis. Supervision by parents on child relationships includes parents having to know who their children are, supervising children's personal phone calls, setting curfew rules and giving penalties if the child violates. Parents also secretly checked children's personal items, even moved children's schools because the school environment was considered to have a bad influence. Monitoring by parents is intended so that children avoid bad relationships and risk the occurrence of unwanted pregnancy, but parents rarely give messages regarding reproductive health and sexuality to their teenagers. Parents are expected to be able to carry out family-based reproductive health and sexuality education to improve adolescents' understanding of the adverse effects and efforts to prevent unwanted pregnancy.